Service Quality of Distributors in the Islamic Perspective (A Study on Retail Consumers in Air Hitam Village, North Sumatra) - Muh Syaukin Muttaqin; Sindy Marchelia Putri; Nurlailah Nurlailah; Susilowati Susilowati; Supriyanto Supriyanto (Sahwahita: Community Engagement Journal, 2025)
This article aims to examine the quality of distributor services provided to retail consumers in Hamlet VIII, Air Hitam Village. The area has approximately five grocery stores that rely on wholesalers in the city to supply daily necessities. The large number of wholesalers in the city creates intense competition among distributors, encouraging them to improve service quality as a strategy to attract and retain customers. In the Islamic perspective, service quality reflects the principle of khidmah, which emphasizes sincere and excellent service. This study uses a qualitative field research approach, with data collected through direct observations and in-depth interviews with grocery store owners who interact directly with distributors. The analysis focuses on five Islamic service characteristics: honesty, responsibility, keeping promises, friendly service, and traders’ attitudes when dealing with customers. The results show that wholesalers in Tanjung Pura City have implemented these Islamic service values in their business practices. As a result, retail consumers experience satisfaction and loyalty, which in turn has a positive impact on the sustainability and competitiveness of distributors.